Brief Report: HIV Incidence Among Older Adults in a Rural South African Setting. (1st September 2020) - Gómez-Olivé, F. Xavier; Houle, Brian; Rosenberg, Molly; Kabudula, Chodziwadziwa; Mojola, Sanyu; Rohr, Julia K.; Clark, Samuel; Angotti, Nicole; Schatz, Enid; Kahn, Kathleen; Bärnighausen, Till; Menken, Jane
Abstract : Introduction: In South Africa, evidence shows high HIV prevalence in older populations, with sexual behavior consistent with high HIV acquisition and transmission risk. However, there is a dearth of evidence on older people's HIV incidence. Methods: We used a 2010–2011 cohort of HIV-negative adults in rural South Africa who were 40 years or older at retest in 2015–2016 to estimate HIV incidence over a 5-year period. We used Poisson regression to measure the association of HIV seroconversion with demographic and behavioral covariates. We used inverse probability sampling weights to adjust for nonresponse in 2015, based on a logistic regression with predictors of sex and age group at August 2010. Results: HIV prevalence increased from 21% at baseline to 23% in the follow-up survey. From a cohort of 1360 individuals, 33 seroconverted from HIV negative at baseline, giving an overall HIV incidence rate of 0.39 per 100 person-years [95% confidence interval (CI): 0.28 to 0.57]. The rate for women was 0.44 (95% CI: 0.30 to 0.67), double than that for men, 0.21 (95% CI: 0.10 to 0.51). Incidence rate ratios (IRRs) again show women's risk of seroconverting double than that of men (IRR = 2.04, P value = 0.098). In past age 60, the IRR of seroconversion was significantly lower than that for those in their 40s (60–69, IRR = 0.09, P value = 0.002; 70–79, IRR = 0.14, P value = 0.010). Conclusions: The risk of acquiring HIV is not zero for people older than 50 years, especially women. Our findings highlight the importance of acknowledging that older people are at high risk of HIV infection and that HIV prevention and treatment campaigns must take them into consideration.